Import-Reducing Effect of Trade Barriers : A Cross-Country Investigation - Wang, Qing (IMF Working Papers; Working Paper ;, 2001)
A comprehensive empirical investigation is carried out to ascertain the import-reducing effect of trade protection barriers. We first present a statistical summary of the status of global trade protection. Then, based on a monopolistic competition trade model and 1994 cross-country data on trade barriers, trade flows, and production, we estimate the import-reducing effect of trade barriers including both tariffs and non-tariff barriers (NTBs). We use the disaggregated cross-country, cross-industry data on manufactured goods and, unlike previous studies, our sample covers a broad range of countries-more than 70 in total-including countries from the most developed ones like those in the Group of Seven to the least developed one, Bangladesh. We specify an empirical model that captures the stylized facts well and helps generate sensible estimates. Our econometric framework is designed to control for the simultaneous determination of trade flows, trade barriers, and production. We find that both tariff and NTBs are quite significant in restricting imports.